How epidemiological patterns shift across populations in an exotic lizard - Bezerra, C. H.; Pinheiro, L. T.; Melo, G. C.; Braga, R. R.; Anjos, L. A. [UNESP]; Borges-Nojosa, D. M. (Cambridge University Press (CUP), 2019)
Several factors influence the dynamics and structure of parasite communities. Our goal was to investigate how the community composition, prevalence and abundance of parasites change across seven populations of the exotic lizard Hemidactylus mabouia in Northeast Brazil, and to describe ontogenetic and sex variations. We found differences in the composition of component communities and patterns of infection according to the host body size across the lizard populations. We did not find any variation between the sexes regarding epidemiological patterns, which can probably be explained by the similar diet and habitat use of male and female H. mabouia. An unusually high abundance and prevalence of trematodes infecting this host lizard was apparent when we compared other native lizard hosts, and we suggest that local environmental conditions might be advantageous to the development and life cycle of these parasites due to the abundance of all the intermediate and definitive hosts.
Keywords: biogeography of parasitism; Helminths; Hemidactylus mabouia